Anpassung: Grundsätzliche Überlegungen zum gottesdienstlichen Feiern im Spannungsfeld von Tradition und Situation = Adaptation : Basic Reflections on Worship in the Challenging Encounter between Tradition and Nowadays Situations - Freilinger, Christoph (Review of ecumenical studies, 2017)
Adaptation of liturgy to conditions of a certain community or society is not only a possibility. Following the Constitution of the Sacred Liturgy of Vatican Council II, it is the very nature and character of the liturgy, which require adaptation to cultural patterns. It is necessary to keep the balance between tradition and present situations, between unity and diversity, between people in their specific circumstances and the heritage of faith of the church.